Flipping the classroom to enhance EFL students’ listening skill - Khoiriyah Khoiriyah (Journal on English as a Foreign Language, 2021)
Studies regarding the use of flipped instruction in language learning have been identified plentifully, little work has examined its use in teaching listening, particularly for specific language testing. In order to address this gap, the impact of the flipped classroom to enhance EFL students’ listening skills, especially language testing, was examined. Furthermore, this study also explored the students’ perspective toward their experience in having a flipped classroom. Accordingly, a mixed-method was employed by using pre-test and post-test after treatment, along with the online open-ended questionnaire. This study revealed that the average score of the post-test (M=72.27) was significantly higher than the average score of the pre-test (64.06), indicating flipped instruction enhances the students' listening comprehension skills. Further, most of the students provoked positive feedbacks on their experience of having flipped classroom. This study might contribute as a guideline for EFL teachers to implement flipped instruction to increase the students' listening comprehension.